EFFORTS MANAGEMENT OF TINEA CORPORIS IN A 16-YEARS-OLD FEMALE PATIENT THROUGH A FAMILY MEDICINE APPROACH AT KUTA MAKMUR PRIMARY HEALTH CENTER, NORTH ACEH REGENCY - Regita Azzahra Nasution (Yayasan Pendidikan Medika Indonesia, 2026)
Patient An. R, 16 years old came to the Kutamakmur Health Center General Polyclinic with complaints of itching in the buttocks about 3 months ago and it has been aggravating since the last 10 days. Initially the complaint appears in the buttocks (buttocks) then slowly extends to the groin. Most of these complaints also appear in the facial area. Initially, the patient felt itching and began to scratch the itchy part so that the bleeding left spots and was felt to be wider and in some parts it looked red with a fairly clear border and accompanied by fine scales. These complaints are quite disruptive to the patient's daily activities. The patient used the same towel as his family member, namely the patient's brother. The patient's brother is a student of the Islamic boarding school who suffers from similar complaints. On physical examination, TD 110/90 mmHg, HR78 x/min, RR 20 x/min, T 36.8°C. On examination of the facial region, eflorescence was seen in the form of hypopigmentation patches and erythematose with firm borders, accompanied by central healing and raised edges with fine squamas. The patient was given therapy, namely ketoconazole cream and oral. Primary data was obtained through anamnesis and physical examination by conducting home visits, filling out family folders, and filling out patient files. The assessment is carried out based on the initial holistic diagnosis, process, and end of the visit, Interventions carried out include education on the importance of clean and healthy living behaviors, avoiding risk factors, adherence to taking medication and avoiding complications that can occur due to tinea corporis.